The Predictive Effects of Reading Motivation Constructs and Reading Practice on Moroccan Fourth Graders Reading Comprehension Achievement: An Analysis of PIRLS 2011 Study (European Journal of Teaching and Education, 2020)
More than any other skill, reading proficiency is important to effectively navigating the school curriculum, shaping each individual’s trajectory through life, and actively taking part in broader society (Martin, Mullis & Hooper, 2011). The aim of the present study is to examine the effects of reading motivation constructs and independent reading practice on predicting Moroccan students’ reading comprehension development. This study is framed within virtuous circle of reading model to explain the interaction between the reading behavior, reading practice and reading comprehension achievement (Stanovich, 1986, 2009). Data of 7805 grade 4 students participating in PIRLS 2011 is analyzed. A multilevel linear regression analysis is used to model the relationship between the investigated variables. These individual factors explain 14% of variance in reading comprehension achievement. Reading motivation constructs particularly reading self-efficacy are found to positively affect reading scores. Further, results indicate that independent reading practice has the most predictive value among all the variables investigated in this study. These findings have important practical implications for the enhancement of reading skills with that of reading self-efficacy.